N-doped porous carbon spheres as metal-free electrocatalyst for oxygen reduction reaction. Issue 9 (8th February 2021) - Ren, Guangyuan; Chen, Shaoqing; Zhang, Junxian; Zhang, Nianji; Jiao, Chuanlai; Qiu, Haifa; Liu, Chongxuan; Wang, Hsing-Lin
Abstract : We demonstrate a template-free strategy to synthesize N-doped carbon spheres by pyrolysis of self-assembled UF resin. The NPCS-900 exhibits excellent ORR electrocatalytic performance both in alkaline and acid solution compared to that of Pt/C. Abstract : The exploration of efficient oxygen reduction reaction (ORR) electrocatalysts with low-cost and facile process is crucial for the commercialization of fuel cells and metal–air batteries. Herein, we demonstrate a template-free strategy to synthesize N-doped porous carbon spheres (NPCS- X, X denotes the pyrolysis temperature) composed of nanosheets via pyrolysis of self-assembled urea formaldehyde (UF) resin as a single precursor. The resultant NPCS-900 exhibits an outstanding electrocatalytic activity towards ORR with a half-wave potential ( E 1/2 ) of 0.87 V ( vs. RHE), superior long-term stability and methanol resistance compared with the commercial Pt/C catalyst in alkaline solution. Furthermore, NPCS-900 also has an impressive ORR electrocatalytic activity and durability in an acid electrolyte. The excellent electrochemical performance of NPCS-900 can be attributed to the abundant exposed active sites of N-species and carbon defects distributed throughout the porous carbon nanosheets of NPCS-900.